A comparative scanning electron microscopy evaluation of smear layer removal with apple vinegar and sodium hypochlorite associated with EDTA - George Táccio de Miranda Candeiro; Isabela Barbosa de Matos; Clarice Fernandes Eloy da Costa; Cristiane Sá Roriz Fonteles; Mônica Sampaio do Vale (University of São Paulo, 2011)
OBJECTIVE: The purpose of this study was to evaluate by scanning electron microscopy (SEM) the removal of smear layer from the middle and apical root thirds after use of different irrigating solutions. MATERIAL AND METHODS: Forty roots of permanent human teeth had their canals instrumented and were randomly assigned to 4 groups (n=10), according to the irrigating solution: apple vinegar (group A), apple vinegar finished with 17% ethylenediaminetetraacetic acid (EDTA) (group B), 1% sodium hypochlorite (NaOCl) finished with 17% EDTA (group C) and saline (group D - control). After chemomechanical preparation, the roots were cleaved longitudinally and their middle and apical thirds were examined by SEM at ×1,000 magnification. Two calibrated examiners (kappa=0.92) analyzed the SEM micrographs qualitatively attributing scores that indicated the efficacy of the solutions in removing the smear layer from the surface of the dentin tubules (1 - poor, 2 - good and 3 - excellent). Data from the control and experimental groups were analyzed by the Kruskal-Wallis and Dunn's test, while the Wilcoxon test was used to compare the middle and apical thirds of the canals within the same group (a=0.05). RESULTS: The middle third presented less amount of smear layer than the apical third, regardless of the irrigant. There was statistically significant difference (p=0.0402) among the groups in the middle third. In the apical third, the apple vinegar/EDTA group showed the greatest removal of smear layer (p=0.0373). CONCLUSION: Apple vinegar associated or not with EDTA was effective in removing smear layer when used as an endodontic irrigant.